Botanic Garden and Band Stand, Trinidad - (:unkn) unknown (G.G. Belgrave, Trinidad, 2009)
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
A view of the Band Stand situated in the Botanical Gardens from the Queen's Park Savannah. The tram tracks in the Savannah would take passengers into "Down Town" Port of Spain.
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Bandstands--Trinidad and Tobago; Street-railroad tracks--Trinidad and Tobago; Queen's Park Savannah